(untitled) (Machine : Jurnal Teknik Mesin, 2020)
Abstract Vacuum infusion is a method of making composite materials by using a vacuum pump to drain and spread the resin in molding. Vacuum infusion can strengthen the mechanical properties of a composite material because the manufacturing process is given a negative pressure which makes the resin or matrix permeate better than the hand lay-up method. Vacuum infusion composites can be used as the main ingredient of a vehicle body due to its strong, flexible nature in its form and manufacture so that it can be shaped as desired. This study examines the effect of vacuum pump pressure on two mechanical properties (impact and bending) of a carbon fiber composite material given an epoxy matrix. The results of this study get an increase in strength of mechanical properties with added vacuum pump pressure. Keywords : carbon fiber, composite, increase in strength, mechanical properties, Vacuum Infusion, vacuum pump pressure.